The effects of cannabinoids on insulin secretion - Anderson, Richard L. (2011)
Type 2 diabetes mellitus is a chronic condition caused by a deficiency in the secretion of insulin from the islets of Langerhans and/or impaired insulin signalling, resulting in hyperglycaemia. The role of the endocannabinoid system is well-recognised in the CNS and immune system, but its role in glucose homeostasis is poorly understood. The aim of this study was to define the roles of cannabinoids in insulin secretion, to provide insights into their therapeutic potential (or limitation) in the treatment of type 2 diabetes.